Linguistic Diversity, Translation and Globalization - Abadou, Fadila (LANGUAGE ART, 2022)
Linguistic diversity is a central issue in globalization that presents major linguistic challenges; among these is the increasing place of dominant languages such as English. To preserve it, we need policies. If we consider its multidisciplinary nature and its communicative function, translation is an authentic activity since it is practised constantly in real life outside classes, and it is the only activity in connection with a foreign language. Thus, the present research aims to investigate the role of translation in preserving linguistic diversity despite the dominance of the English language.